2014
DOI: 10.1016/j.nbd.2013.09.007
|View full text |Cite
|
Sign up to set email alerts
|

DJ-1 ameliorates ischemic cell death in vitro possibly via mitochondrial pathway

Abstract: DJ-1 is an important redox-reactive neuroprotective protein implicated in regulation of oxidative stress after ischemia. However the molecular mechanism, especially the mitochondrial function, by which DJ-1 protects neuronal cells in stroke remains to be elucidated. The aim of this study was to reveal whether DJ-1 translocates into the mitochondria in exerting neuroprotection against an in vitro model of stroke. Human neural progenitor cells (hNPCs) were initially exposed to oxygen–glucose deprivation and repe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…Mitochondrial alterations could lead to cellular energy deficit or oxidative stress, resulting in cell death. We and others have demonstrated mitochondrial dysfunction after experimental stroke. Mitochondrial dysfunction following stroke has been associated with reduced number and size of mitochondria in astrocytes , neuronal mitochondrial swelling and fragmentation , excitotoxic calcium entry overload , and deficient astrocytic support to neuronal functions .…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Mitochondrial alterations could lead to cellular energy deficit or oxidative stress, resulting in cell death. We and others have demonstrated mitochondrial dysfunction after experimental stroke. Mitochondrial dysfunction following stroke has been associated with reduced number and size of mitochondria in astrocytes , neuronal mitochondrial swelling and fragmentation , excitotoxic calcium entry overload , and deficient astrocytic support to neuronal functions .…”
Section: Discussionmentioning
confidence: 62%
“…Adding knowledge regarding the role of mitochondria in post‐stroke EC degeneration by categorizing their abnormal morphologies might lead to the use of mitochondrial condition as a potential biomarker of BBB alterations after stroke as well as for determining treatment effect(s). On the other hand, targeting mitochondria per se might be a potent therapeutic approach for stroke . In fact, we showed that intravenous transplantation of hBMEPCs into tMCAO rats significantly decreased abnormal mitochondria, resulting in increased numbers of mitochondria with normal morphology within ECs and perivascular astrocytes.…”
Section: Discussionmentioning
confidence: 90%
“…DJ-1 may protect NSCs during proliferation through its antioxidant activity. Indeed, DJ-1 plays a role in the protection against oxidative stress and oxygen-glucose deprivation in human NPCs in culture [299] and DJ-1 deficiency in murine ESCs causes increased sensitivity to oxidative stress (increased apoptotic cell death after H 2 O 2 treatment) and to proteasomal inhibition (increased sensitivity to the proteasomal inhibitor lactacystin) [300]. These results underline the importance of this protein in the protection of these highly proliferative cells against accumulation of deleterious ROS or accumulating proteins.…”
Section: Dj-1 (Park7)mentioning
confidence: 99%
“…There have been conflicting reports of both increase [28] and decrease [29] in the amount of PARK7 in cerebrospinal fluid in sporadic PD patients as compared with control groups. Secreted PARK7 plays important physiological and pathophysiological roles which include involvement in anti-oxidative effects [30], extracellular signaling between neighboring neuronal cells [31], angiogenic and osteogenic factors [32], and degradation of aggregated protein [26]. Such findings indicate that PARK7 secretion may be implicated in the etiology and/or progression of diseases such as PD and cancer, possibly making it suitable for use as a biomarker.…”
Section: Introductionmentioning
confidence: 99%